2013
DOI: 10.1007/s10815-013-9971-7
|View full text |Cite
|
Sign up to set email alerts
|

Do estrogen receptor alpha polymorphisms have any impact on the outcome in an ART program?

Abstract: Purpose To investigate two of the most studied estrogen receptor alpha polymorphisms (PvuII and XbaI) in combination, in order to evaluate their impact on an ART program outcome. Methods 203 normally ovulating women who underwent IVF or ICSI treatment were genotyped for PvuII and XbaI polymorphisms in ESR1 intron 1 using Real-Time PCR. The relationship between the presence of polymorphic alleles and the ovulation induction parameters and outcome was examined. Results Women were grouped according to the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Compared with the three studies that also analyzed the ERS2 XbaI, Anagnostou et al [ 33 ] similarly showed association between the mutated G allele with worst quality embryos and lower levels of estradiol on the hCG day, which is different from Altmae et al [ 28 ], who found a larger dose of estradiol on the hCG day and per follicle in the GG genotype [ 28 , 33 ]. As discussed earlier, the difference in the results might be due to the exclusion of patients with endometriosis and older than 38 years of age by our study, as it can significantly change the response to COH.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Compared with the three studies that also analyzed the ERS2 XbaI, Anagnostou et al [ 33 ] similarly showed association between the mutated G allele with worst quality embryos and lower levels of estradiol on the hCG day, which is different from Altmae et al [ 28 ], who found a larger dose of estradiol on the hCG day and per follicle in the GG genotype [ 28 , 33 ]. As discussed earlier, the difference in the results might be due to the exclusion of patients with endometriosis and older than 38 years of age by our study, as it can significantly change the response to COH.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, a different approach was used by Anagnoston in 2013 when he evaluated the number of mutated alleles of PvuI and XbaI and the results of COH/IVF in 203 women. The mutated alleles C (Pvul) and G (Xbal) were associated with the worst quality embryos and smaller estradiol levels on the hCG day [ 33 ]. To prepare this analysis they considered that the two genes had necessarily the same behavior as wild and mutated alleles, a fact that has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Other predictive markers of ovarian response are polymorphisms of the alpha gene of ESR (ESR1); rs2234693, also known as the PvuII restriction polymorphism, and rs9340799, also known as the XbaI restriction polymorphism. Both these polymorphisms have been reported to be associated with the risk of infertility (Anagnostou et al 2013). For the third SNP, the microsatellite length polymorphism ESR1 (TA)n, the longer ESR1 (TA) n microsatellite repeat polymorphism has been reported to be associated with an improved ovarian response to FSH.…”
Section: Introductionmentioning
confidence: 99%